Grön humaniora: En inledning till fältet - Nordlund, Christer (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2016)
Environmental humanities is a dynamic and rapidly growing post-disciplinary field of scholarship that brings together scholars, practices and theoretical perspectives from the humanities, social sciences and the fine arts. It analyses, explores and tackles questions related to the environment and all kinds of environmental problems, and it may thus be understood as a concerted response to the pressing environmental challenges of our time. This article gives a brief introduction to the field and the various ways it has been promoted and institutionalized in Sweden and abroad. It also introduces the articles in the present issue, written by the researchers Sverker Sörlin, Ebba Lisberg Jensen, Martin Hultman, Coppélie Cocq and Daniel Andersson, as well as a short essay and a review. Taken together, these texts represent one of the first publications on environmental humanities and its development, published in Swedish.